The Effect Of Stock Price, Share Trading Volume And Stock Return Volatility On Bid-Ask Spread On Lq45 Companies Listed On Idx In 2019 - Dhea Zatira; Sustari Alamsyah; Eni Suharti (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to determine the effect of stock prices, stock trading volume, and stock return volatility on the bid-ask spread on the LQ45 index of companies listed on the Indonesia Stock Exchange. The period used in this study is four quarters during 2019. The technique used in sampling is by using purposive sampling and obtained 32 companies. The data analysis technique used is multiple linear regression analysis. The results showed that partially the stock price had a negative and significant effect on the bid-ask spread as indicated by the t-count value of -3.964077 > t-table 1.649 and the value of Prob. 0.001 < 0.05 . The stock trading volume variable partially has no effect on the bid-ask spread as indicated by the t-count value of 0.177347 < t Table 1.649 and the value of Prob. 0.8595 > 0.05. Then the stock return volatility variable has no effect on the bid-ask spread as indicated by the t arithmetic value of 0.634639 < t Table 1.649 and the value of Prob. 0.5268 > 0.05. Simultaneously F-statistic 5.93433 > F Table 2.68 and the value of Prob (Fstatistic) 0.000814 <0.05, it can be concluded that the variables of Stock Price (X1), Stock Trading Volume (X2) and Stock Return Volatility (X3) jointly affect the Bid-Ask Spread (Y).